Sparisoma choati, a new species of Parrotfish (Labridae: Scarinae) from the tropical eastern Atlantic - Rocha, Luiz A.; Brito, Alberto; Robertson, D. Ross (Zootaxa, 2012)
The parrotfish Sparisoma choati is described from the tropical eastern Atlantic Ocean. It is genetically unique and alsodiffers from its congeners by coloration as follows: initial phase individuals and females greyish brown to greyish red,with chin and belly paler and reddish brown scales irregularly distributed along flanks resulting in a general mottled ap-pearance; terminal phase individuals with brownish red head and upper half of anterior two-thirds of body, ventral portionof central third of body bright yellow-green, posterior third of body dark greenish gray and dark spot on upper fifth ofpectoral fin base. The new species is found in rocky reefs along the coast and oceanic islands off West Africa, from Cape Verde and Senegal south to the islands of São Tomé and Príncipe and Angola.